EFEKTIVITAS METODE QUANTUM LEARNING DALAM MENINGKATKAN HAFALAN ASMAUL HUSNA PADA SISWA MI KELAS VI MI AL IKHWANIYAH TANGERANG SELATAN - Hakim, Fikri; Islamianti, Dian (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2024)
This study aims to examine the effectiveness of the application of the Quantum Learning method in improving memorization of Asmaul Husna in grade VI students of MI Al Ikhwaniyah. The purpose of this study was to test whether this learning method can improve students' memorization and understanding results related to the meaning of Asmaul Husna. This study used an experimental method with a one-group pre-test and post-test design. The research sample was taken purposively, involving 25 grade VI students who had difficulty memorizing and understanding Asmaul Husna. Data collection was carried out through observation of student activity and memorization tests before and after treatment. The results showed a significant increase in students' memorization abilities after the application of Quantum Learning, with an average pre-test score of 53.6 and a post-test increase to 81.6. In addition, the percentage of classical completeness increased from 24% in the pre-test to 96% in the post-test. The results of the inferential statistical test with the t-test showed a t-count value of 3.00, greater than the t-table of 2.06, which indicates that this method is effective in improving students' memorization of Asmaul Husna. In conclusion, Quantum Learning has a significant effect on improving memorization and understanding of Asmaul Husna